2005
DOI: 10.1111/j.1741-1130.2005.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Policy Shifts on South Asian Carers in the United Kingdom

Abstract: The aim of this study was to assess how the introduction of new service policies in the United Kingdom – such as person‐centered planning and the active development of support networks – was impacting the lives of carers of people with intellectual disability from South Asian backgrounds. Using a semistructured interview schedule, 19 families of South Asian background living in an urban conurbation were interviewed about their service use and needs with respect to providing care for their family member with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 6 publications
1
12
1
Order By: Relevance
“…With the exception of two participants, who were no longer living at home, none were dissatisfied with services. This is in contrast with the views of parents from previous research, who have expressed dissatisfaction with services ( Hatton et al, 1998, Hensel et al, 2005and Raghavan & Waseem, 2007.…”
Section: Theme 3 (Sub-theme1): Following and Noticing Rulescontrasting
confidence: 55%
“…With the exception of two participants, who were no longer living at home, none were dissatisfied with services. This is in contrast with the views of parents from previous research, who have expressed dissatisfaction with services ( Hatton et al, 1998, Hensel et al, 2005and Raghavan & Waseem, 2007.…”
Section: Theme 3 (Sub-theme1): Following and Noticing Rulescontrasting
confidence: 55%
“…Perhaps as a symptom of systemic discrimination, whereby information is not appropriately provided, McGrother et al (2002) found that South Asians tend to underutilise services available to them due to their own lack of knowledge of the cause or concept of having an ID, often interchanging it with mental health problems. In a study by Hensel, Krishnan, Saunders, Durrani, and Rose (2005) a large proportion of families had different understandings about ID, many were unable to provide diagnostic information on their child and only able to give vague descriptions. This issue may be confounded by belief structures within south Asian culture which include, for some, alter-casting (Goffman, 1963) linked to the fear parents from south Asian backgrounds have of being stigmatised for having a child with ID, as well as beliefs of 'past life wrong-doings', termed as 'karma' in the Hindu religion (Gabel, 2004).…”
Section: Cultural Issuesmentioning
confidence: 99%
“…Linked to fear of stigma of having ID, is the cultural norm of 'shame' attached to accessing health and social care provision and a fear that other people will 'find out' that a family member has an ID (Hensel et al, 2005). Although it is questionable as to whether this relates to all South Asian families (with no concrete data proving this), Gable (2004) suggests that overall South Asians' cultural desire for privacy is demonstrated in the ways they approach (and avoid) health professionals.…”
Section: Cultural Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative research, typically within specific minority ethnic communities, has tended to look to cultural factors to account for these elevated levels of parental risk (e.g. Harry 1992;Magana 1999;Gabel 2004;Hensel et al 2005).…”
Section: Introductionmentioning
confidence: 99%